Lightweight reduced graphene oxide-Fe3O4 nanoparticle composite in the quest for an excellent electromagnetic interference shielding material. (16th April 2018) - Singh, Ashwani Kumar; Kumar, Ajit; Haldar, Krishna Kamal; Gupta, Vinay; Singh, Kedar
Abstract: This work reports a detailed study of reduced graphene oxide (rGO)-Fe3 O4 nanoparticle composite as an excellent electromagnetic (EM) interference shielding material in GHz range. A rGO-Fe3 O4 nanoparticle composite was synthesized using a facile, one step, and modified solvothermal method with the reaction of FeCl3, ethylenediamine and graphite oxide powder in the presence of ethylene glycol. Various structural, microstructural and optical characterization tools were used to determine its synthesis and various properties. Dielectric, magnetic and EM shielding parameters were also evaluated to estimate its performance as a shielding material for EM waves. X-ray diffraction patterns have provided information about the structural and crystallographic properties of the as-synthesized material. Scanning electron microscopy micrographs revealed the information regarding the exfoliation of graphite into rGO. Well-dispersed Fe3 O4 nanoparticles over the surface of the graphene can easily be seen by employing transmission electron microscopy. For comparison, rGO nanosheets and Fe3 O4 nanoparticles have also been synthesized and characterized in a similar fashion. A plot of the dielectric and magnetic characterizations provides some useful information related to various losses and the relaxation process. Shielding effectiveness due to reflection (SER ), shielding effectiveness due to absorption (SEA ), and total shielding effectiveness (SET ) were also plotted against frequency over a broad range (8–12 GHz). A significant change in all parameters (SEA value from 5 dB to 35 dB for Fe3 O4 nanoparticles to rGO-Fe3 O4 nanoparticle composite) was found. An actual shielding effectiveness (SET ) up to 55 dB was found in the rGO-Fe3 O4 nanoparticle composite. These graphs give glimpses of how significantly this material shows shielding effectiveness over a broad range of frequency.